Foreign direct investment, exports, education, and growth in Malaysia - Yusoff, Mohammed (Inderscience, 2014)
Although it has been recognised that foreign direct investment (FDI), exports, and education are important ingredients in economic development, not much research has been carried out in developing countries to determine the effects of these three variables, taken together, on economic growth. Most of these studies focus on the effects of exports on growth or FDI on growth or exports: education on growth, and FDI on growth. This paper examines the relationship of these three variables together on economic growth using the cointegration technique, VECM, and the causality tests. The results suggest that real GDP per capita, exports, FDI and education spending are cointegrated. The estimated long-run relationship shows that exports, FDI and education expenditure could explain the variation in real GDP per capita. Both the Granger and Toda-Yamamoto causality tests support the hypothesis that exports, FDI and education expenditure cause economic growth with no feedback. These imply that the Malaysian export-oriented, liberal FDI and education development strategies have played important role in the development of Malaysian economy.